Mengidentifikasi Kesulitan Belajar Anak Usia 5-6 Tahun Di TK Negeri Fajar - Fuzy Apriliani; Rifka Ainunida; Wini Yuliantika; Nurhayati Nurhayati (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
This study aims to identify learning difficulties experienced by children aged 5-6 years at TK Negeri Fajar. The method used is qualitative, a research method with a case study approach. The data source consisted of one class teacher, and 2 children who had learning difficulties. Data collection techniques in this study were carried out through observation, interviews and documentation. The results of this study indicate different learning difficulties in children in the 5-6 year age group. For example, it is difficult to recall the information provided by the teacher in learning, it is difficult to recognize the shapes of letters and also interpret them, the forms of letters they write are sometimes illegible, it is difficult to arrange numbers in learning activities, and it is difficult to understand the concept of heavy and light and also simple directions such as left and right, up and down. All of these things are very influential in class learning activities. The role of schools in dealing with children who have learning difficulties is to take an approach that can also provide specific assignments, give responsibility and invite children to actively participate in learning.